Hoop stress test on new high strength alloy laminated Bi-2223 conductor. (15th June 2015) - Miyoshi, Y; Nishijima, G; Kitaguchi, H; Chaud, X
Abstract: Bi-2223, despite its high field transport performance, lacks mechanical strength and relies on lamination technology for applications where both current density and mechanical strength are important. The hoop stress limits of a newly available high-strength Bi-2223 has been measured by two different methods at LNCMI-Grenoble and Tsukuba Magnet Laboratory. The measurements confirm the new conductor's high tensile strength up to 400 MPa. We discuss briefly the role of bending strain with the aid of a supplementary hoop stress measurement with reduced winding diameter.